Synchronization, channel estimation and detection for ultra-wideband systems - Ekrem, Ersen. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Timing acquisition and synchronization of ultra-wideband UWB signals within nanosecond accuracy pose a major impediment. Noise is assumed to be additive white Gaussian noise (AWGN) in all of the works in spite of that impulsive noise in indoor environments. Therefore, we propose two robust acquisition algorithms. These receivers rely on robust estimation techniques and transmitted reference (TR) methodology. Then, the algorithms are extended to multiuser environments by assuming multiuser interference (MUI) as a white Gaussian random variable (r.v.) invoking central limit theorem (CLT). The another point about synchronization of UWB signals is the multiuser synchronization under intersymbol interference (ISI). Two iterative synchronization algorithms are proposed for chip-level interleaved UWB signals subject to ISI and MUI. One of the algorithms is blind and the other is data-aided both of which are soft input soft output (SISO) devices. Moreover, data-aided approach uses the training sequence to form an initial estimate of the a posteriori probabilities (APPs) of the time-delays. Another challenge for UWB is the channel estimation due to high number of parameters to be estimated. Most of the attention is devoted to non-coherent demodulation or frequency-domain (FD) techniques due to their low-complexities. But most of the works do not present a detailed comparison of time-domain (TD) and FD channel estimation and assume that noise is AWGN. Therefore, the robust FD and TD recursive channel estimators are presented with their convergence analysis. Moreover, robust detectors are designed and their probability of error performance is investigated.
Keywords: Signal detection.; Time-domain analysis.; Ultra-wideband devices.; Random noise theory.; Synchronization.